Implementasi Nilai-Nilai Pancasila dalam Perkembangan Partai Politik dan Pemilihan Umum di Indonesia - Situmorang, Lidia Kristiani; Humayah, Humayah; Khairiyah, Tsany Khalisha; Ayuningsih, Pitri; Edelweiska, Rinjani; Husna, Zahrotul; Yulyanti, Putri (Peneliti.net, 2024)
In Implementation of Pancasila Values in the Development of Political Parties and General Elections in Indonesia. Currently, the values of Pancasila are often underestimated and are no longer understood in depth, in fact the Indonesian people and citizens only know and only know formally that Pancasila is a basis whose values are of very high and noble value because it is not without the reasons and excuses of its predecessors. initiated Pancasila as the basis of the state. Pancasila is expected to become a reference and basis for the Indonesian state's steps in the future. However, currently Pancasila only has 5 principles which are the basis and are not studied by Indonesian citizens themselves. Therefore, with this research, researchers want to see the extent to which successful political parties participate in respecting and understanding the values of Pancasila and implementing these Pancasila values. With this research aims to find out: 1. implementation of Pancasila values in the development of a political party, 2. The role of Pancasila in the world of politics, Political Parties in interpreting Pancasila principles in policies and agendas in the Prosperous Justice Party, 3. Prosperous Justice Party The real. This research uses descriptive research with a qualitative approach. The results of this research show that: 1. In implementing the values of Pancasila, it plays an important role in the world of politics in Indonesia, 2. Pancasila influences voters' views on voting in general elections, 3. The Prosperous Justice Party has implemented its agenda and authority.